Deciphering the stratified distribution and evolution of deep soil drought and its environmental controls: New evidence from continuous fiber optic monitoring in 0–30 m profile - Yongping Tong; Yunqiang Wang; Jingxiong Zhou; Meina He; Ting Wang; Yuting Xu; Xiangyu Guo; Mengya Sun; Zimin Li; Bin Shi (Geoderma)
Regulating soil drought regime is essential for global ecology and climate security. Indeed, soil drought is largely dependent on rapid climate change, complex soil types, and interaction with vegetations, leading to its spatial and temporal heterogeneity. Previous studies paid less attention on temporal-frequently and spatial-deeply investigations, therefore causing information omission when studying soil drought. This study deployed Fiber Bragg Grating sensors in a 0–30 m profile to monitor deep soil drought with daily resolution under a Robinia pseudoacacia forest in the Chinese Loess Plateau. We aimed at deciphering the distribution, evolution, and determinants of soil drought in an extremely deep profile surpassing the region’s deepest root range. Our experiment identified three typical drought characteristic layers within the deep loess profile: 0–0.4 m (L1), 0.4–1.8 m (L2), and 1.8–30 m (L3). Soil desiccation indices in all three layers of L1, L2, and L3 were 3.56, 0.37, and −0.92, respectively. No drought was observed in L1, while L2 exhibited the most frequent drought changes, and L3 showed a stable and severe drought. These results reveal that both distribution and evolution of deep soil drought exhibited the significant stratified characteristics. For the drought in the entire profile, roots, soil organic carbon, and bulk density acted as the primary factors influenced its spatial distribution. The temporal dynamics of drought were more significantly influenced by temperature, wind speed, and relative humidity than by precipitation. Our analytical results also indicated that synergistic impacts existed when the aforementioned factors affected soil drought distribution and evolution. Considering heterogeneous characteristics and determinants in diverse layers, we suggest a ‘Soil Characteristic Layer Identification–Stratified Governance’ strategy during ecological recovery, to strike a water demand balance between vegetation restoration and soil drought regulation. Our findings therefore offer a reference for deep soil drought evaluation and regulation in loess regions worldwide.